Spatial dynamics and mixing of bluefin tuna in the Atlantic Ocean and Mediterranean Sea revealed using next‐generation sequencing. (22nd February 2018) - Puncher, Gregory N.; Cariani, Alessia; Maes, Gregory E.; Van Houdt, Jeroen; Herten, Koen; Cannas, Rita; Rodriguez‐Ezpeleta, Naiara; Albaina, Aitor; Estonba, Andone; Lutcavage, Molly; Hanke, Alex; Rooker, Jay; et al.
Abstract: The Atlantic bluefin tuna is a highly migratory species emblematic of the challenges associated with shared fisheries management. In an effort to resolve the species' stock dynamics, a genomewide search for spatially informative single nucleotide polymorphisms (SNPs) was undertaken, by way of sequencing reduced representation libraries. An allele frequency approach to SNP discovery was used, combining the data of 555 larvae and young‐of‐the‐year (LYOY) into pools representing major geographical areas and mapping against a newly assembled genomic reference. From a set of 184, 895 candidate loci, 384 were selected for validation using 167 LYOY. A highly discriminatory genotyping panel of 95 SNPs was ultimately developed by selecting loci with the most pronounced differences between western Atlantic and Mediterranean Sea LYOY. The panel was evaluated by genotyping a different set of LYOY ( n  = 326), and from these, 77.8% and 82.1% were correctly assigned to western Atlantic and Mediterranean Sea origins, respectively. The panel revealed temporally persistent differentiation among LYOY from the western Atlantic and Mediterranean Sea ( F ST  = 0.008, p  = .034). The composition of six mixed feeding aggregations in the Atlantic Ocean and Mediterranean Sea was characterized using genotypes from medium ( n  = 184) and large ( n  = 48) adults, applying population assignment and mixture analyses. The results provide evidence of persistent population structuring across broad geographic areas and extensive mixing in the Atlantic Ocean, particularly in the mid‐Atlantic Bight and Gulf of St. Lawrence. The genomic reference and genotyping tools presented here constitute novel resources useful for future research and conservation efforts.